Endoscopic Assisted Unilateral Transpedicular Microdiscectomy for a Patient of Thoracic Disc Herniation with Paraplegia - Rahman, Moshiur; SIM, Khairun Nabi Khan; Khan, Robert Ahmed; Sarker, Mainul Haque; Moscote-Salazar, Luis Rafael (Archives of Clinical and Medical Case Reports, 2020)
Background: Disc herniation of the thoracic spine is a rare lesion that is believed to occur in 1 in 1000 to 1 in 1,000,000 patients each year. Endoscopic-assisted thoracic disc microdiscectomy is a safe and effective surgical removal technique for intervertebral herniated thoracic discs. Case Presentation: A 48-year-old female was presented with progressive weakness in both lower limbs for three months, incapacity to void urine for 2 weeks. She had back pain and neck pain for 5 years. Clinically, she was diagnosed with paraplegia at stage D6/7 as a case of dorsal disc prolapse. After doing unilateral transpedicular microscopic discectomy she recovered over 4 weeks and her muscle strength was 4/5 in the lower limbs, and she was able to walk. Conclusion: Thoracic disc herniations are relatively uncommon compared with lumbar and cervical disc pathologies. Although it has posed significant problems for spinal surgeons, the adoption of minimally invasive thoracic disc resection procedures may result in decreased operating time, reduced blood loss, and faster patient recovery.